2012
DOI: 10.1007/s10545-012-9533-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of 355 mucopolysaccharidosis patients reveals 104 novel mutations

Abstract: Mucopolysaccharidosis (MPS) disorders are heterogeneous and caused by deficient lysosomal degradation of glycosaminoglycans, resulting in distinct but sometimes overlapping phenotypes. Molecular analysis was performed for a total of 355 MPS patients with MPSI (n = 15), MPSII (n = 218), MPSIIIA (n = 86), MPSIIIB (n = 20), MPSIVA (n = 6) or MPSVI (n = 10). This analysis revealed 104 previously unreported mutations: seven in IDUA (MPSI), 61 in IDS (MPSII), 19 in SGSH (MPSIIIA), 11 in NAGLU (MPSIIIB), two in GALNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 37 publications
4
34
0
1
Order By: Relevance
“…(Arg468Gln)ClinVar ID:10498[71]Pathogenicc.1478G>Cp. (Arg493Pro)[46]Likely pathogenicc.1563A>Tp. (Glu521Asp)NovelLikely pathogenicDeletion of the whole IDS gene[56]PathogenicHomologous recombination IDS-IDS2[36]PathogenicDeletion ex 1–7 (2 deletions in tandem with 2 duplications 1.2 Mb distally to IDS gene)[74]Pathogenic SGSH (NM_000199.4; NP_000190.1)c.118T>Ap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Arg468Gln)ClinVar ID:10498[71]Pathogenicc.1478G>Cp. (Arg493Pro)[46]Likely pathogenicc.1563A>Tp. (Glu521Asp)NovelLikely pathogenicDeletion of the whole IDS gene[56]PathogenicHomologous recombination IDS-IDS2[36]PathogenicDeletion ex 1–7 (2 deletions in tandem with 2 duplications 1.2 Mb distally to IDS gene)[74]Pathogenic SGSH (NM_000199.4; NP_000190.1)c.118T>Ap.…”
Section: Resultsmentioning
confidence: 99%
“…(Arg468Gln)Severe (P20)Severe [71]; severe [57]; severe [67]; four severe patients [63]; severe [34]; three severe patients [35]; severe [31]; severe [25]; severe [18]c.1478G>Cp. (Arg493Pro)Severe (P17)Phenotype not reported [46]SGSHc.197C>Gp. (Ser66Trp)Severe (P27)Two severe, three intermediate, one unknown [17]c.220C>Tp.…”
Section: Resultsmentioning
confidence: 99%
“…It includes the major mutation types that were previously described in larger MPSII series and nine small and ‘private’ novel changes, one novel exon 1 deletion or c.(−217_103del), one unknown splicing defect, one chimeric IDS‐IDSP1 allele and four complete IDS / IDSP1 deletions that were delineated using microarray analysis (Table ). The four point mutations that occur at CpG dinucleotides identified in this study (4/10; 40%) are highly recurring C > T or G > A transitions in the MPSII cases according to LOVD and HGMD registries; thus, they are considered to be ‘hot spots’ . This proportion of C > T or G > A transitions at CpG dinucleotides is consistent with 47% of the previously reported pathogenic variants at IDS .…”
Section: Discussionmentioning
confidence: 99%
“…An examination of patients with Hunter syndrome showed that exon 3 of the IDS gene had significantly more mutations than that of other exons [8]. The patients with MPS II have a wide range of symptoms caused by the disease affecting multiple different organ systems.…”
Section: Introductionmentioning
confidence: 99%